Warning symptoms preceding out-of-hospital cardiac arrest: Do patient delays matter? - Nehme, Z.; Bernard, S.; Andrew, E.; Cameron, P.; Bray, Janet; Smith, K. (Elsevier, 2018)
Background: Although increasing patient delays between symptom onset and activation of emergency medical services (EMS) can lead to poorer outcomes following acute myocardial infarction, its effect in out-of-hospital cardiac arrest (OHCA) populations is unclear. Methods: Between 1st January 2003 and 31st December 2011, we included adult patients with anginal warning symptoms and subsequent EMS witnessed OHCA of presumed cardiac aetiologyfrom the Victorian Ambulance Cardiac Arrest Registry. Multivariable logistic regression was used to assess the impact of patient delay time (i.e. symptom onset to EMS call time) on survival to hospital discharge. Results: A total of 1056 EMS witnessed OHCA were screened, of which 515 (48.8%) reported chest pain or anginal equivalent symptoms. The median patient delay time was 25 min (interquartile range [IQR] 9–89 min), and did not differ across survivors and non-survivors. However, patients in lowest quartile of patient delay (≤8 min) also experienced significantly higher rates of non-shockable arrest rhythms and circulatory compromise. A total of 16 baseline and clinical characteristics were tested in a multivariable model of survival to hospital discharge, of which, only six were retained in the final model, including: age, dyspnoea, vomiting, shockable arrest rhythm, systolic blood pressure, and patient delay time. Every 30 min increase in patient delay time was independently associated with a 2.3% (95% CI: 0.4%, 4.1%; p = 0.02) reduction in the odds of survival to hospital discharge. Among patients with ST-segment deviation on the pre-arrest ECG, every 30 min increase in patient delay time was associated with a 3.4% reduction in the odds of survival (OR 0.966, 95% CI: 0.937, 0.996; p = 0.03). Conclusion: Increasing delays in activating EMS before the onset OHCA may be associated with reduced survival. Future research could explore whether increasing public awareness of the warning symptoms leads to earlier medical contact for OHCA.